2021
DOI: 10.3390/plants10102064
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Characterization of the Rice Chalcone Isomerase Family

Abstract: Chalcone isomerase (CHI) is a key enzyme in flavonoid biosynthesis. In plants, CHIs occur in multigene families, and they are divided into four types, types I–IV. Type I and II CHIs are bona fide CHIs with CHI activity, and type III and IV CHIs are non-catalytic members with different functions. Rice contains seven CHI family genes (OsCHIs). Molecular analysis suggested that OsCHI3 is a type I CHI, and the other OsCHIs were classified into types III and IV. To elucidate their biochemical functions, OsCHI1, OsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Functional diversification after gene expansion could occur at the transcriptional level. To date, 12 differentially expressed CHIs in G. max [ 25 ], 5 tissue-specific CHIs in A. thaliana [ 15 ], 33 CHIs in cotton [ 32 ], 7 CHIs in rice [ 33 , 34 ], 30 CHIs in six Citrus species [ 35 ], 31 CHIs in liverwort and Selaginella species [ 18 ], 56 CHIs in fern species [ 26 ], and 11 CHIs in D. cambodiana [ 36 ], have been reported. These observations showed that CHIs usually have tissue-specific expression in various tissues, and often respond to various environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional diversification after gene expansion could occur at the transcriptional level. To date, 12 differentially expressed CHIs in G. max [ 25 ], 5 tissue-specific CHIs in A. thaliana [ 15 ], 33 CHIs in cotton [ 32 ], 7 CHIs in rice [ 33 , 34 ], 30 CHIs in six Citrus species [ 35 ], 31 CHIs in liverwort and Selaginella species [ 18 ], 56 CHIs in fern species [ 26 ], and 11 CHIs in D. cambodiana [ 36 ], have been reported. These observations showed that CHIs usually have tissue-specific expression in various tissues, and often respond to various environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…With the sequencing of plant genomes and transcriptomes, more and more plant CHI family genes have been discovered from many species, including primitive seedless plants and higher seed plants. To date, 12 CHIs in Glycine max [ 25 ], 5 CHIs in Arabidopsis thaliana [ 15 ], 33 CHIs in cotton [ 32 ], 7 CHIs in Oryza sativa [ 33 , 34 ], 30 CHIs in six Citrus species [ 35 ], 31 CHIs in liverwort and Selaginella species [ 18 ], 56 CHIs in fern species [ 26 ], and 11 CHIs in Dracaena cambodiana [ 36 ], have been identified based on their corresponding genomic or transcriptomic data. Acquisition of CHI enzymatic activity in plants during evolution is an intriguing topic, because both type III and type IV CHIs are devoid of bona fide CHI catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are biosynthesized by phenylpropanoid, starting from phenylalanine [ 61 ]. Chalcone synthetase is the first enzyme in flavonoid biosynthesis and catalyzes the formation of chalcones from one molecule of p-coumaroyl-CoA and three molecules of malonyl-CoA [ 62 ]. Depending on the degree of oxidation of the central nucleus, flavonoids are classified into flavones, flavanones, flavonols (proanthocyanidins), dihydroflavonols, isoflavones, isoflavanones, chalcones, aurones, anthocyanidins and tannins ( Supplementary Figure S1 ) [ 63 , 64 , 65 , 66 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…CHS is known to catalyse the first step in the flavonoid biosynthetic pathway to produce naringenin chalcone [60]. Next, CHI catalyses the isomerisation of chalcones into (2S)-flavanones that serve as the precursor to various flavonoids in plants [61]. Rice and maize are monocots containing CHS and CHI gene families from their genomes.…”
Section: Case Study: Application Of Co-expression Network In Biologic...mentioning
confidence: 99%
“…precursor to various flavonoids in plants [61]. Rice and maize are monocots containing CHS and CHI gene families from their genomes.…”
Section: Case Study: Application Of Co-expression Network In Biologic...mentioning
confidence: 99%